Ecology, morphology and distribution of Anisota finlaysoni Riotte (Lepidoptera, Saturniidae) - Schmidt, B. Christian; Gartshore, Mary (Zootaxa, 2025)
Identifying the conservation needs of the short-horned oakworm, Anisota finlaysoni Riotte, has been hampered by incomplete resolution of species boundaries and geographic ranges of the Anisota senatoria species-group. Here, the life history, morphology, occurrence, and DNA barcode variation of A. finlaysoni and A. senatoria are compared across a transect of three key geographic regions in Ontario, Canada. Contrary to recent range depictions, our results show that A. finlaysoni is currently confirmed to occur only in the region of eastern Lake Ontario’s north shore. Previous information on morphological characters used to distinguish A. finlaysoni is incomplete or erroneous. Lake Erie populations most recently assigned to A. finlaysoni exhibit some finlaysoni-like larval traits, but adult phenotype of all examined material is indistinguishable from A. senatoria of the Lake Huron region, and unlike topotypical A. finlaysoni. Although the cryptic occurrence of A. finlaysoni in the Lake Erie region cannot be ruled out, current data indicate that this species has a much smaller global range than previously believed, and is separated by a geographic gap of about 200 km from the nearest A. senatoria populations. Re-assignment of the Lake Erie populations from A. finlaysoni to A. senatoria, and the recognition of some peripheral occurrence records as historical errors, results in a significantly smaller global range for A. finlaysoni. DNA barcode data for the genus Anisota are at odds with current taxonomy, limiting the utility of barcodes in discriminating species of the senatoria-group. Because A. finlaysoni is distinct morphologically as adults and larvae from geographically nearby populations of A. senatoria, it should continue to be treated as a distinct species pending convincing evidence to the contrary.